Promoting L2 learners’ critical thinking skills: the role of social constructivism in reading class - Le, Ha Van; Nguyen, Long Quoc (Frontiers in Education, 2024)
In the rapidly evolving digital landscape, the imperative for success has increasingly spotlighted the essential need for students to develop critical thinking and reading skills as key competencies for the 21st century. This study sought to explore the potential of constructivism to enhance learners' critical thinking and reading abilities, alongside evaluating their receptiveness to this pedagogical approach. Utilizing a mixed-methods research design that combines a quasi-experimental framework with semi-structured interviews, the investigation yielded two principal findings. First, it was determined that the constructivist approach significantly outperformed traditional teacher-centered methods in promoting critical thinking skills among students. Second, the majority of participants reported a high level of satisfaction with the constructivist method, attributing this to the approach's facilitation of deeper knowledge acquisition and increased opportunities for interaction with peers and instructors. Theoretical implications of this study underscore the value of constructivism in fostering an engaging and interactive learning environment conducive to the development of critical analytical skills. Practically, the findings advocate for educational practitioners and institutional leaders to consider the integration of constructivist strategies in reading sessions, aiming to bolster students' critical thinking and reading competencies. Moreover, it emphasizes the necessity for educators to receive comprehensive training on the nuances of constructivist pedagogy to ensure its effective implementation. This study thus contributes to the pedagogical discourse by affirming the efficacy of constructivism in enhancing critical cognitive skills and by outlining a pathway for its successful adoption in educational settings.